Community case management of chest indrawing pneumonia in children aged 2 to 59 months by community health workers: study protocol for a multi-country cluster randomized open label non-inferiority trial - Nisar, Yasir Bin (International Journal of Clinical Trials, 2020)
Background: The World Health Organization (WHO) integrated management of childhood illness (IMCI) protocol recommends treatment of chest indrawing in 2-59 months old children with oral amoxicillin by trained health facility workers. Whereas, the WHO/UNICEF integrated community case management (iCCM) protocol recommends referral by community level health workers (CLHWs) to a health facility. This study aims to evaluate whether CLHWs can treat chest indrawing pneumonia effectively and safely. Methods: This multi-centre cluster randomized controlled open label, non-inferiority trial will be conducted in Bangladesh, Ethiopia, India and Malawi. All sites will use a common protocol with the same study design, participants, intervention, control and outcomes. CLHWs will identify 2-59 months old children with chest indrawing. Study supervisors, trained in the iCCM protocol, will confirm CLHWs’ findings. Pulse oximetry will be used to identify hypoxaemic children. In the intervention group, enrolled children will be treated with oral amoxicillin for 5 days, and in the control group they will be referred to a health facility, after providing first dose of oral amoxicillin. An independent outcome assessor will visit each enrolled child on days 6 and 14 of enrolment, to assess study outcomes. Conclusions: If CLHWs can effectively and safely treat chest indrawing pneumonia in 2-59 months old children, it will increase access to pneumonia treatment substantially, as in many settings, health facilities and trained health workers are not easily accessible. Moreover, this evidence will contribute towards the review of the current iCCM protocol and its harmonization with the IMCI protocol. Trial Registration: The trial is registered at AZNCTR International Trial Registry as ACTRN12617000857303.